2015
DOI: 10.1007/s10463-015-0534-9
|View full text |Cite
|
Sign up to set email alerts
|

Conditional sure independence screening by conditional marginal empirical likelihood

Abstract: In many applications, researchers often know a certain set of predictors is related to the response from some previous investigations and experiences. Based on the conditional information, we propose a conditional screening feature procedure via ranking conditional marginal empirical likelihood ratios. Due to the use of centralized variable, the proposed screening approach works well when there exist either or both hidden important variables and unimportant variables that are highly marginal correlated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…To simplify the notation, we use Ûi,jk = [X ij − E(X j |x iC )]Y ik . Similar to the proof of Lemma 4 inHu and Lin (2017) and using the similar technique in the proof of Lemma 4.1, we can prove that P{ l c j (0) < 2t} ≤ P…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…To simplify the notation, we use Ûi,jk = [X ij − E(X j |x iC )]Y ik . Similar to the proof of Lemma 4 inHu and Lin (2017) and using the similar technique in the proof of Lemma 4.1, we can prove that P{ l c j (0) < 2t} ≤ P…”
mentioning
confidence: 71%
“…To avoid such a risk, statisticians developed the model-free methods, some typical works include but are not limited to Li et al (2012), Cui et al (2015), Lu and Lin (2017), Pan et al (2019) and the reference therein. Additionally, to reduce the negative effect caused by the complicated correlation among predictors, researchers also put forward some conditional screening methods, see Barut et al (2015), Hu and Lin (2017), Lin and Sun (2016) and Lu and Lin (2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical likelihood method usually can improve the confidence region, can increase the accuracy of coverage, can be implemented easily, and can be studentized automatically. There have been many literary works that discuss the empirical likelihood method and its applications, for example, An and Zhao (); Cui, Guo, Lin, and Zhu (); Hu and Lin (); Kiwitt and Neumeyer (); Lian (); and Liu and Xia ().…”
Section: Estimation Methodologymentioning
confidence: 99%
“…Since then, conditional screening method has drawn much interest and various conditional screening approaches have been proposed under different scenarios. For example, Hu and Lin (2017), Liu and Wang (2018), and Lu and Lin (2020) developed different conditional screening procedures for ultrahigh-dimensional complete data, Liu and Chen (2018) considered the conditional quantile independence screening approach for ultrahigh-dimensional heterogeneous data, and Hong et al (2018) developed a conditional screening method for censored survival data under the proportional hazards model. Simulation studies demonstrated that these conditional screening approaches can provide a powerful means to identify hidden active variables for ultrahigh-dimensional data.…”
Section: Introductionmentioning
confidence: 99%